Penerapan Metode Composite Performance Index (CPI) Dalam Sistem Pendukung Keputusan Pemilihan Kepala Desa Terbaik Kabupaten Bengkulu Utara - Andre Pranat Andre pranata; Reno Supardi; Jhoanne Fredricka (Jurnal Media Infotama, 2024)
North Bengkulu Regency has a list of village heads who serve as village heads. Based on the current list of village heads in North Bengkulu Regency, the best village head will be selected. The problem faced in this research is that in selecting the best village head we only look at the abilities of the village head, even though there are several criteria that can be considered by the district in selecting the best village head. The criteria used in this research are Integrity (C1), Commitment to advancing the village (C2), Ability to manage village resources (C3), Work attitude (C4). To overcome the problems encountered, a decision support system is needed. The method used in this research is the Composite Performance Index (CPI) method, this method uses 54 criteria, namely: Integrity, Commitment to advancing the village, Ability to manage village resources, Work attitude. From the results of the research, the decision results were obtained with the best alternative, namely A5 in the name of Sugeng R with a value of 218.3333333